ANALISIS STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN JUMLAH KONSUMEN - Devvy, Novia (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
ABSTRACT The objective of research was to find out: (1) how the Marketing Communication Strategy is in increasing the number of consumers in Solo Grand Mall, (2) the factors encouraging the Marketing Communication Strategy undertaking in Solo Grand Mall, (3) the constraints in Marketing Communication Strategy in Solo Grand Mall, and (4) the attempts taken to cope with the constraints in Marketing Communication Strategy in Solo Grand Mall.This study employed a qualitative research, with descriptive method, and single embedded research strategy. The sampling technique used was purposive sampling technique. The data sources used in this research were informant, place or event, place or location, document or archive. Techniques of collecting data used were interview, observation, documentation, and library study. The data validation was conducted using data and method triangulations. Technique of analyzing data used was a flowing interactive analysis.Considering the result of research, it could be concluded that: (1) the marketing communication strategy in Solo Grand Mall could be divided into 2 stages: (a) Planning by conducting SWOT analysis and determining the Strategy, Targeting and Positioning, (b) implementation by conducting marketing communication mix including advertising, sales promotion, event, and public relations. (2) The factors encourage the performance of marketing communication activity in Solo Grand Mall included: (a) to increase the number of visitors as the competitor?s malls emerge, (b) to look for profit for the company, (c) to help tenant in selling product, (d) to improve the company?s image. (3) The constraints in performing the marketing communication activity in Solo Grand Mall included: (a) technical constraints, (b) internal communication disconnection because of individual preoccupation, (c) the consumer?s less interesting in event or activity held, (d) creative idea should be raised to create something that can attract the consumer?s interest, (e) limited bureaucracy in event organization, (f) sneaky hands that damaged the outdoor media, (g) less clear event schedule. (4) The attempts taken to deal with the constraints occurring in the implementation of marketing communication activity included: (a) to keep improving in order to deal with the technical constraints, (b) to hold coordination meeting, (c) to make an evaluation on each activity conducted, (d) to broaden the insight and knowledge about marketing mix, (e) to maturate the event planning, (f) to reinforce the Corporate Social Responsibility in order to improve the company?s image, (g) to keep conforming to the event organizers.Keywords: Strategy, Communication, Marketing, Solo Grand Mall